Upaya Meningkatkan Keaktifan Mengikuti Layanan Informasi Bimbingan dan Konseling Melalui Media â€œPuzzleâ€ pada Siswa - Nurbowo Budi Utomo (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2015)
Â This study focused on: "media puzzle modification to increase the activity following the information guidance and counseling services". Modifications made to the content of media puzzle, shapes, how to play and igredients.The purpose of this study is 1) Improve student activity following the information guidance and counseling services with media modifications puzzle. 2) th increase results in service results in the form of knowledge (understanding), a positive attitude (comfortable) and a plan of action (action). Students at grade 8th-I as study subjects, which has been implementing the 2013 curriculum. The research approach is Action Research, as much as two cycles. The data required in this research is data active learners who obtained using observation with sheet instrument, then the data of the service that was obtained through the test instrument, non test. Results of the study as follows: 1) Modification of media information services puzzle in guidance and counseling can increase active learners. 2) Puzzle modification in guidance and counseling information services can improve service results. The results of this study can be used as reference material for the school counselor to develop media in guidance and counseling services as well as enhance the activity of students in participating in the information services of guidance and counseling in schools.